2012
DOI: 10.1111/j.1752-248x.2012.01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic band syndrome associated with orofacial clefts: a report of two cases

Abstract: This article presents two cases of amniotic band syndrome associated with orofacial deformities. There was an uncommon presentation in one of them as Tessier nos. 5, 7 and 30 with irregularly distributed amniotic facial band. The surgical repair of the facial clefts and difficulties in overall management in our environment are further discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The index cases probably resulted from late insult as they had only limb involvement. Unlike the index cases, other authors [22][23][24][25] have reported more severe cases with associated facial clefts and central nervous system involvement. As in the index cases, Askins and Ger 26 found that the distal extremities were most often affected while Foulkes and Reinker 27 reported that in their seventy year review of ABS, a third of their seventy one patients had lower limb involvement.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The index cases probably resulted from late insult as they had only limb involvement. Unlike the index cases, other authors [22][23][24][25] have reported more severe cases with associated facial clefts and central nervous system involvement. As in the index cases, Askins and Ger 26 found that the distal extremities were most often affected while Foulkes and Reinker 27 reported that in their seventy year review of ABS, a third of their seventy one patients had lower limb involvement.…”
Section: Discussionmentioning
confidence: 89%
“…Musculoskeletal disorders commonly associated with ABS include club foot, syndactyly (as seen in the second case) or acrosyndactyly, hypoplastic nails or fingers, pseudoarthrosis of underlying bones, peripheral nerve defects, distal lymph oedema, intra-uterine amputations (as seen in the first case), cleft lip and palate and umbilical hernia. 28 As in the first case, Herrara et al 29 also reported a case of ABS with amputation of the right leg while Adeosun et al 25 in Maiduguri, Northern Nigeria reported two cases with amputation of the fingers and toes.…”
Section: Discussionmentioning
confidence: 95%
“…Management of patients with ABS requires a multidisciplinary approach with a collaborative medical/dental team. Depending on its severity and the malformations present, the team is integrated by diverse specialists, such as Orthodontists, Pediatric Surgeons, Plastic and Maxillofacial Surgeons, Ophthalmologists, Neurologists, Geneticists, and Psychologists [ 22 , 23 ]. In addition to being familiar with ABS, Pediatric Dentists must also collaborate actively, both in the prevention and the rehabilitation of oral-dental anomalies, bearing in mind the importance of active early intervention [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic band syndrome is a constellation of congenital anomalies, which may be subtle or extensive. [ 1 2 ] We hereby, report a case of amniotic band constriction over face and scalp in an infant leading to facial asymmetry. The rare occurrence of amniotic band constriction prompted us to report the case.…”
mentioning
confidence: 99%
“…Clinically, ABS can manifest in numerous forms, the commonest ones being distal ring constrictions, deformities in the limbs, and amputations. [ 2 ] Rare findings include syndactyly, lymphedema, clubfoot, cleft lip and palate, pseudo-arthrosis, peripheral nerve palsy, dislocation of hip, and craniofacial synostosis. [ 7 ] Rarely, internal organs may be affected.…”
mentioning
confidence: 99%